2008
DOI: 10.1002/ejic.200800564
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Catalytic Dehydrogenation of the Guanidine–Borane Adducts H3B·hppH (hppH = 1,3,4,6,7,8‐hexahydro‐2H‐pyrimido[1,2‐a]pyrimidine) and H3B·N(H)C(NMe2)2: A Combined Experimental and Quantum Chemical Study

Abstract: Herein thermal and catalytic dehydrogenation of the guanidine–borane adducts H3B·hppH (hppH = 1,3,4,6,7,8‐hexahydro‐2H‐pyrimido[1,2‐a]pyrimidine) and H3B·N(H)C(NMe2)2 are analysed. Thermal decomposition of H3B·hppH at 80 °C leads to [HB(μ‐hpp)]2 and a second boron hydride, which is tentatively identified as [(κ2N‐hpp)BH2]. Decomposition in boiling toluene (110 °C) leads to a mixture of [H2B(μ‐hpp)]2 and [HB(μ‐hpp)]2, from which [H2B(μ‐hpp)]2 can be separated and crystallised. In the presence of a catalyst (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 31 publications
(37 reference statements)
1
24
0
2
Order By: Relevance
“…One such example is provided by thermal decomposition of the tetramethylguanidine-borane adduct sketched in Equation (1). [11] The BH 3 group migrates to one of the amino N atoms. Then a 1,4-dehydrogenation reaction follows leading to decomposition to give finally (HBNMe) n oligomers.…”
Section: Methodsmentioning
confidence: 99%
“…One such example is provided by thermal decomposition of the tetramethylguanidine-borane adduct sketched in Equation (1). [11] The BH 3 group migrates to one of the amino N atoms. Then a 1,4-dehydrogenation reaction follows leading to decomposition to give finally (HBNMe) n oligomers.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal as well as catalytic dehydrogenation were studied. [9] For reversible dihydrogen addition the thermodynamic properties of the reaction are calculations, and we also analyse the possibility of further reductive dehydrogenation to give the double base-stabilized diboranes (4) [BH(µ-tbo)] 2 and [BH(µ-tbn)] 2 or oligomeric H 2 B(µ-tbn) 2 BH{BH(µ-tbn) 2 BH} n BH(µ-tbn) 2 quite important. The H 2 addition should be associated with a standard Gibbs energy close to zero to allow addition and elimination at low temperatures and pressures (of course subject to a sufficiently low activation barrier or the possibility to decrease the barrier with the aid of a catalyst).…”
Section: Introductionmentioning
confidence: 99%
“…The initial thermal dehydrogenation of 1 proved not to be the ideal route to 3; however, we recently showed that 1 can be catalytically dehydrogenated with [{Rh(1,5-cod)Cl} 2 ] in toluene at 80 8C to give 2 (with a B···B separation of 306.5 pm). [8] This species, dissolved in toluene, can be further dehydrogenated at 114 8C in the presence of catalytic amounts of [{Rh(1,5-cod)Cl} 2 ] to yield 3 [Eq. (1)], with a BÀB bond distance of 177.2 pm, in a clean reaction.…”
mentioning
confidence: 99%
“…The molecular structures of 1, 2, and 3 from X-ray diffraction results. [7,8] [a] The energy-minimum structures were calculated at the B3LYP/6-31 + + G** level. The d( …”
mentioning
confidence: 99%